Analisis wacana ekokritik: Representasi alam dan ideologi pembangunan dalam pidato Menteri Pertanian “Amran Sulaiman” (tentang penurunan harga pupuk 20%) - Dian Nur Lestari; Saptono Hadi; Agus Hermawan; Redhitya Wempi Ansori (Patria Educational Journal (PEJ), 2026)
This study analyzes ecological discourse in a speech by the Minister of Agriculture, Amran Sulaiman, regarding a policy to reduce fertilizer prices by 20%. Employing a descriptive qualitative approach with Garrard’s ecocritical framework, the study examines how nature is represented within a narrative of productivity. The findings reveal a discursive contradiction: on the one hand, the policy is positioned as support for farmers; on the other hand, it reinforces an anthropocentric development ideology that views nature merely as a commodity input. The study further shows that government narratives remain dominated by a technocentric logic, which has the potential to trigger long-term environmental degradation in pursuit of short-term economic stability.